The Multifaceted Nature of Weight-Related Self-Stigma: Validation of the Two-Factor Weight Bias Internalization Scale (WBIS-2F) - Meadows, Angela; Higgs, Suzanne (Frontiers in Psychology, 2019)
Background: Internalised weight stigma (IWS) is generally operationalised as self-devaluation due to weight in higher-weight individuals. The most commonly used measure of IWS, the Weight Bias Internalization Scale (WBIS), was developed from an original pool of 19 items. Item selection was guided by statistical techniques based upon an a priori hypothesised unidimensional factor structure. The resulting 11-item scale mostly assesses appearance-related attitudes, fear of stigma, affect, and desire for change, all of which may be a natural response to societal weight stigma, even in the absence of self-devaluation. Items pertaining to self-blame, stigma awareness, perceived legitimacy of weight stigma, and most items pertaining to self-worth, were excluded from the final scale. It is unclear whether an a priori assumption of multi-dimensionality would have produced different results. Methods: Exploratory and confirmatory factor analysis of the original 19-item questionnaire were conducted in 931 higher-weight individuals. Results: A 13-item two-factor structure was identified. Factor 1 comprised seven items that could be loosely conceived as weight-related distress. Factor 2 comprised six items, all of which pertained to weight-related self-worth. Tested individually, the six items making up the Self-devaluation factor were an excellent fit for the data on all fit indices. Conclusion: Internalised weight stigma is a multi-dimensional construct. The Two-Factor Weight Bias Internalization Scale (WBIS-2F) provides options to explore the relationships between different aspects of IWS and upstream and downstream variables. The Self-Devaluation subscale is suitable for standalone use when weight-related self-devaluation per se is the construct of interest.